1977
DOI: 10.1073/pnas.74.7.3038
|View full text |Cite
|
Sign up to set email alerts
|

Fatty liver induced in Zucker "fatty" (ff) rats by a semisynthetic diet rich in sucrose.

Abstract: A new fatty liver model is described in which heredity plays a major role. A marked fatty liver develo s when the homozygous mutant Zucker rat (ff or "fatty") is fe a semisynthetic diet enriched in sucrose. Lean littermates do not develop fatty livers on this experimental diet. Even old ff rats do not develop fatty livers on chow; the experimental diet is required. The fatty liver is described, including light microscopic and preliminary electron microscopic observations. The clinical importance of understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…Feeding the animals with cornstarch or with Eurylon (high-amylose starch) did not prevent the development of obesity. When the animals were fed the sucroserich diet, the triglyceride concentration in the liver was very high (22.3 and 88.9 mg/g for lean and obese rats, respectively) [14], in accord with another report [16]. Feeding cornstarch strikingly reduced this concentration in both lean and obese Zucker rats (Table 1).…”
Section: Discussionsupporting
confidence: 75%
“…Feeding the animals with cornstarch or with Eurylon (high-amylose starch) did not prevent the development of obesity. When the animals were fed the sucroserich diet, the triglyceride concentration in the liver was very high (22.3 and 88.9 mg/g for lean and obese rats, respectively) [14], in accord with another report [16]. Feeding cornstarch strikingly reduced this concentration in both lean and obese Zucker rats (Table 1).…”
Section: Discussionsupporting
confidence: 75%
“…Short-term (1-3 weeks) consumption of this diet caused Zucker (fa/fa) rats to develop hepatic steatosis with no apparent infiltration of inflammatory cells nor fibrosis. Hepatic steatosis in this model must be due to such a high content of sucrose (85.7 cal% to carbohydrate) in the diet, an unusual amount in human daily diets (12). On the other hand, the ratio of disaccharides (17.4 cal% to carbohydrate) contained in the synthetic diet used in our study is common in the human daily diet, compared to the MCD diet and the diet reported by Novikoff.…”
Section: Discussionmentioning
confidence: 72%
“…According to our view that the MCD diet, HFD, and diet reported by Novikoff (12) do not correspond to the diets imposed by human lifestyles, we fed a synthetic diet that can be considered for human consumption, to obese, diabetic Zucker (fa/fa) rats. In most major models of NASH, such as MCD diet-fed rats, the animals lose body weight.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations